Effect of Word of Mouth on Consumer Buying Behavior - Aslam, Saad; Jadoon, Ehtisham; Zaman, Khalid; Gondal, Shehryar (Mediterranean Journal of Social Sciences, 2011)
The objective of this study is to examine the negative and positive affect of word of mouth marketing on consumer buyingbehaviour. The study is based on primary data collected from one hundred households and university students from the area of Rawalpindiand Islamabad cities of Pakistan. The data is analyzed using the techniques of frequency distribution and ranking. The result reveals thatconsumers tend to rely on word of mouth for the purchase of everyday items as well as long-term goods. The people that seem to have aninfluence on the decision of the consumers the most are closed family, friends and acquaintances. Results further show that a bitterexperience of a product/place can create problems for the company as it is a major factor of negative word of mouth. Viral Marketing isgaining rapid popularity among consumers as it’s depicts in the results. Finally, a negative word of mouth travels faster than positivecomments.